Analysis of Sustainable Ecotourism Business Development in the Perspective of Ecotourism Development Governance in Gunung Pancar Natural Tourism Park - Hidajati, Nurrul; B. Sukamdani, Hariyadi; Dewi Dyah Maharani, Maya; Eddyono, Fauziah; Prihartadi , Bambang (International Journal of Social Service and Research, 2026)
This study aims to evaluate the governance strategy of Gunung Pancar Nature Tourism Park, Bogor, West Jawa in achieving sustainability. This research is motivated by financial losses that have occurred over the past three years and the low realization of work, which has only reached 25%, even though the management has absorbed 75% of the local community’s workforce and obtained a 20-year license extension starting in 2024. The research uses a mixed-methods approach through Importance–Performance Analysis (IPA), in-depth interviews, and SWOT analysis, involving four stakeholders: managers, local communities, visitors, and related agencies. The results of the IPA show that aspects requiring primary attention include the clarity of leadership vision and mission, consistency of management actions, and consideration of impacts in decision-making. In addition, various operational aspects—such as community empowerment programs, environmental education, conservation, strengthening human resource capacity, negative impact control, and monitoring and evaluation—have not been running optimally. The results of the in-depth interviews indicate that the low realization of work is influenced by weak monitoring and evaluation, as well as management distractions due to land conflicts. The absorption of local labor is also considered less effective because the community only plays a role as a technical implementer without capacity building and has not been involved in the decision-making process. Based on the SWOT analysis, the ecotourism governance recovery strategy includes implementing a single-gate system to eliminate illegal levies and improve profitability, restructuring community involvement, and strengthening human resource capacity and education.